The relationship between peptic ulcer and cardiovascular disease in elderly population: a study on mortality and disease development - Lin He; Qianlei Wang; Yang Qiu; Nan Shen; Peimin Pu; Ruiqing Wang; Hongyu Miao; Haiyan Zhang; Xiao Yu; Dinghong Xiao; Lianjun Xing; Zhidong Liu (Frontiers in Medicine)
BackgroundPeptic ulcer (PU) and cardiovascular disease (CVD) are significant chronic illnesses, particularly in the elderly. This study investigates the relationship between PU and CVD in older adults and the impact on mortality risk.MethodsThis study was conducted utilizing data from a nationwide health survey of the elderly in China. Kaplan–Meier curves and log-rank tests were applied in survival analysis to evaluate mortality differences between the groups. Stratified models were applied to evaluate the effects of factors.ResultsThis study included 3,636 participants. CVD was significantly associated with an increased PU risk (OR = 1.31, 95%CI 1.03–1.66, p = 0.04), while PU had no significant effect on CVD incidence (OR = 1.08, 95%CI 0.77–1.51, p = 0.64). Mortality risk was significantly higher in the CVD group (HR = 1.22, 95%CI 1.03–1.45, p = 0.02) compared to the non-comorbid group. No significant difference in mortality was observed between the PU-only and combined PU-CVD groups. Stratified analysis identified advanced age (≥75 years) (HR = 1.45, 95%CI 1.06–1.87, p < 0.01) and male gender (HR = 1.29, 95%CI 1.05–1.62, p < 0.01) as significant mortality risk factors among PU patients.ConclusionPU does not have a significant impact on overall mortality or the prognosis of CVD patients. CVD was a risk factor for PU, but PU did not significantly increase CVD risk. A higher mortality risk was observed in older and male PU patients. These findings suggest the need for gender-sensitive and age-stratified management strategies for PU in high-risk groups.